Fractured - McKenzie, Catherine (Lake Union Publishing, 2016)
After moving with her family across the country to Cincinnati to get away from a stalker, novelist Julie Prentice seems to click with her new neighbor, until a series of misunderstandings lead Julie and her family to become the victims of troubling harassment.